Uslūb Majāz Aqlī Dalam Penafsiran Al-Qur’an: Kajian Struktural Dan Hermeneutis - Mario Mega Zaputra; Mohamad Harjum; Andi Miswar (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
Background: Majāz aqlī is one of the prominent rhetorical devices in the Qur’an, characterized by attributing an action to an agent other than its actual doer. When interpreted literally, this linguistic phenomenon may lead to misunderstanding and theological inaccuracies, making it necessary to examine its structural mechanisms and interpretive functions. Purpose of the Study: This study aims to analyze the structural patterns of Majāz aqlī and to examine its hermeneutical significance in Qur’anic interpretation. Methods: This research employs a qualitative library-based approach using a bayani linguistic framework. The data are derived from classical balaghah treatises, classical Qur’anic commentaries, and contemporary tafsir works. The analysis focuses on identifying patterns of attribution (isnād) and examining their implications for interpretation. Results: The study finds that Majāz aqlī in the Qur’an operates through systematic attribution to causes, places, objects, and instruments. Each structural pattern serves specific rhetorical and interpretive functions, such as emphasizing causality, highlighting outcomes, and enriching expressive meaning. Conclusions: Understanding Majāz aqlī is essential for preventing literalistic misinterpretation and theological error. This study demonstrates that Majāz aqlī functions not merely as a rhetorical ornament, but as a hermeneutical mechanism that bridges linguistic structure and theological meaning in Qur’anic interpretation.